Acute and chronic Graft-versus-host disease after hematopoietic stem cell transplantation - Funke,Vaneuza A. M. (2016)
ABSTRACT graft-versus-host disease (GVHD) is one of the main complications of hematopoietic stem cell transplantation, affecting about 50% to 80% of the patients. Acute GVHD and its clinical manifestations are discussed in this article, as well as the new NIH criteria for the diagnosis and classification of chronic GVHD. Therapy for both chronic and acute GVHD is an important field of discussion, as there is no proven superiority for the majority of therapies used after primary treatment has failed. Hence, this review is meant to be a useful consultation tool for hematologists dealing with this complex transplantation procedure complication.